Inseminação artificial em tempo fixo com uso de uma ou duas doses de sêmen em vacas holandesas - (:unkn) unknown (Universidade Federal do Pampa, 2012)
Tha aim of this work was to evaluate the pregnancy rate of Holstein cows, in lactation, with Artificial Insemination in Fixed Time (AIFT), using two semen pailletes at cows that manifested estrus between withdrawal of PRID and the AIFT itself. Two groups of cows were synchronized: the first (Group I), was inseminated with one paillette; the second (Group II) was inseminated with two. Both groups received at the first day (day 0) the Progesterone Intravaginal Device (PRID), and 2 ml of Estradiol Benzoate. On the 8th day the PRID was removed, and 400 IU of Equine Chorionic Gonadotropin (ECG) and 2ml of Prostaglandin F2α were applied, and on day10: 1ml of gonadotrophin releasing hormone (GnRH) in cows that did not exhibit estrus. These three managements (days 0, 8, 10) were performed at 7 o’clock in the morning, and the AIFT itself was performed on the 10th at 15:00 pm. On Group 2, animals were monitored for detection of estrus and insemination 12 hours after, and the second dose at programmed time for AIFT. In the pregnancy diagnostic it was obtained 41% pregnancy rate for Group I, and 62% for Group II. It can be concluded that there was no statistical difference between treatments.
Keywords: Inseminação; Sêmen; Prenhez; Vacas Holandesas; Insemination; Pregnancy; Holstein Cows; CNPQ::CIENCIAS AGRARIAS